It's a numbers game!. Baseball : the math behind the perfect pitch, the game-winning grand slam, and so much more! - Buckley, James, Jr., 1963- (National Geographic kids., 2021)
Investigates mathematical principles behind the sport of baseball, discussing statistics, scores, and calculations. Includes color photographs, infographics, fact boxes, sports history, math activities, and a baseball glossary.